2021
DOI: 10.1108/ijilt-04-2021-0057
|View full text |Cite
|
Sign up to set email alerts
|

Student learning outcomes and online engagement in time of crisis: the role of e-learning system usability and teacher behavior

Abstract: PurposeThis research explores the effect of e-learning Moodle-based system usability on students' learning outcomes with the possible intervening role of teacher's behavior and online engagement.Design/methodology/approachIn this research, the authors followed a quantitative methodology and a deductive research approach. Data were collected from 433 students at different study levels and academic specializations in higher education institutions (HEIs) in Oman. The data have been analyzed using partial least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 85 publications
3
6
0
Order By: Relevance
“…Moreover, study results show that students' perceptions of teachers' indigenous knowledge enhance their classroom engagement. These findings can be related to the previous studies that suggested the significance of teachers' behaviors and student-teacher relationships in determining and enhancing students' level of engagement in classrooms (Dahleez et al, 2021;Roorda et al, 2017). Suppose the students are satisfied with the teachers and consider that the teachers possess the required indigenous knowledge of the literature they are going to teach.…”
Section: Findings Of the Studysupporting
confidence: 75%
See 4 more Smart Citations
“…Moreover, study results show that students' perceptions of teachers' indigenous knowledge enhance their classroom engagement. These findings can be related to the previous studies that suggested the significance of teachers' behaviors and student-teacher relationships in determining and enhancing students' level of engagement in classrooms (Dahleez et al, 2021;Roorda et al, 2017). Suppose the students are satisfied with the teachers and consider that the teachers possess the required indigenous knowledge of the literature they are going to teach.…”
Section: Findings Of the Studysupporting
confidence: 75%
“…Finally, the results showed that students' engagement bridges their perception of teachers' indigenous knowledge and cultural competencies and the learning outcomes. The previous research also supports the mediatory role of students' engagement between teachers' behaviors and competencies and students' performance (Dahleez et al, 2021;Roorda et al, 2017;Wasike, 2017). Hence, when the students positively perceive that their teachers have the required indigenous knowledge of the subject, they are teaching and possess variable cultural competencies.…”
Section: Findings Of the Studysupporting
confidence: 54%
See 3 more Smart Citations